Prevalence of Cervical Cancer Screening Among Women in Fishing Communities of Entebbe Municipality, Wakiso District. A Cross-sectional study. - Keneema , Emily; Lwenge , Mathias; Nanyunja, Zaitune; Kawoozo, Barbara; Immaculate, Ampeire; Ssetaala, Ali; Mpendo, Juliet; Okech, Brenda; Okodan, Daniel (Student's Journal of Health Research Africa, 2022)
Background: Cervical cancer disease in Uganda remains the leading causes of deaths among cancer patients, responsible for about 4,607 deaths annually. Despite the numerous modern treatment options and prevention strategies, cervical cancer screening prevalence remains undefined especially in the fishing communities and yet women living in fishing communities are core interest groups for cervical cancer due to their relatively higher risk of HIV and HPV infections. Methodology: A cross-sectional study employing a quantitative approach was performed, purposive sampling following a household survey was conducted. Structured interviews and questionnaires were administered to collect data from June 2021 to August 2021. Data were analyzed in SPSS version 25 using the log-binomial model. Results: prevalence of cervical cancer screening among women in fishing communities of Entebbe municipality, Wakiso district remains as low as 23.2%, mainly unsatisfactory among the married women (aPR = 0.232 [0.13 - 0.43], p < 0.001) and, Catholics (aPR = 0.050 [0.01 - 0.18], p < 0.001). At the same time, higher cervical cancer screening prevalence was observed among employed women (aPR= 2.81 [1.48 - 5.33], p = 0.002), those who had prior recommendation from healthcare workers (aPR = 1.25 [0.09 - 0.65], p = 0.004), and those who perceived that cervical cancer is a curse from God (cPR = 2.800 [CI = 1.798 - 4.36], P = 0.000). Conclusion: Cervical cancer screening is low among women in fishing communities of Entebbe municipality; only 2 in every 10 women have ever been screened for cervical cancer in their lifetime, while less than 1 in 10 had to follow-up of screening. Recommendation: Behavior change communication preferably using the intrapersonal channel on issues related to cervical cancer screening should be adopted in the fishing communities urgently if we are to elevate the uptake of this secondary prevention measure for cervical cancer.